2013
DOI: 10.2298/ciceq120403066g
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ferric iron precipitation in bioleaching process using partial least squares and artificial neural network

Abstract: A quantitative structure-property relationship (QSPR) study based on partial least squares (PLS) and artificial neural network (ANN) was developed for the prediction of ferric iron precipitation in bioleaching process. The leaching temperature, initial pH, oxidation/reduction potential (ORP), ferrous concentration and particle size of ore were used as inputs to the network. The output of the model was ferric iron precipitation. The optimal condition of the neural network was obtained by adjusting various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A quantitative structure-property relationship study based on partial least squares method and the results revealed that the developed model shows high reliability and good predictivity for ferric iron prediction in the bioleaching system. 24 Pre-oxidation efficiency of refractory gold concentrate by ozone in ferric sulfate solution was predicted efficiently with the use of ANNs. Here, the inputs of the network were ozone concentration, Fe 3+ concentration, solid-liquid ratio, aeration (O 2 ), leaching duration, and temperature whereas the percentage of iron extracted from the gold concentrate is the output of the network.…”
Section: Abstract Electronic Waste Printed Circuit Boards Bimentioning
confidence: 99%
“…A quantitative structure-property relationship study based on partial least squares method and the results revealed that the developed model shows high reliability and good predictivity for ferric iron prediction in the bioleaching system. 24 Pre-oxidation efficiency of refractory gold concentrate by ozone in ferric sulfate solution was predicted efficiently with the use of ANNs. Here, the inputs of the network were ozone concentration, Fe 3+ concentration, solid-liquid ratio, aeration (O 2 ), leaching duration, and temperature whereas the percentage of iron extracted from the gold concentrate is the output of the network.…”
Section: Abstract Electronic Waste Printed Circuit Boards Bimentioning
confidence: 99%
“…Utilizing backpropagation ANN, prediction models were constructed and applied in sintering pot experiments to optimize humidity and fuel ratio, ultimately improving sintering drum strength. Golmohammadi et al [ 29 ] developed a Quantitative Structure–Property Relationship (QSPR) using Partial Least Squares (PLS) and ANN to predict the precipitation of trivalent iron during bioleaching. The neural network model exhibited reliable and accurate predictive capabilities during the bioleaching process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quantitative structure-property relationship (QSPR) method was used in many fields to extract and link chemicals properties to their molecular structures [22][23][24][25][26][27][28][29][30]. In QSPR modelling different computational techniques have been used, such as multiple linear regression (OLS or MLR), PLS, ANN, SVR and ANFIS [31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%